Does Osgood-Schlatter Disease exist in the dog? - Pfeil, von D. J. F.; DeCamp, C. E.; Diegel, K. L.; Gholve, P. A.; Probst, C. W.; Déjardin, L. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2009)
Osgood-Schlatter disease (OSD) is a condition affecting human adolescents in which there is partial separation of bone fragments from the tibial tuberosity at the site of insertion of the patellar ligament to the tibial tuberosity. Tensile trauma seems to be the most likely aetiology. Clinical signs in people consist of swelling and pain at the proximal part of the tibial tuberosity and around the distal end of patellar ligament. Radiographs frequently show small ossicles at the patellar ligament insertion. Conservative treatment is usually curative. The term OSD has also been used for the canine patient. However, radiographs of these patients typically show an enlarged radio-lucent line at the apophyseal plate of the tibial tuberosity. This finding is consistent with a mild avulsion fracture of the canine tibial tuberosity. Based on the radiographic differences between the two species, it seems more appropriate to use the term OSD only for people. The purpose of this paper is to review the literature on OSD in people and the reports of injuries to the proximal tibial tuberosity in dogs. In addition, a new classification system for tibial tuberosity avulsion injuries in the immature dog is proposed, with an algorithm for management of this injury.
Keywords: Osgood-Schlatter disease; avulsion; dog; tibial tuberosity; apophysis